Genome-Wide Identification of TCP Transcription Factors Family in Sweet Potato Reveals Significant Roles of miR319-Targeted TCPs in Leaf Anatomical Morphology - Ren, Lei; Wu, Haixia; Zhang, Tingting; Ge, Xinyu; Wang, Tianlong; Zhou, Wuyu; Zhang, Lei; Ma, Daifu; Wang, Aimin (Frontiers in Plant Science, 2021)
Plant-specific TEOSINTE BRANCHED/CYCLOIDEA/PCF (TCP) transcription factors play vital roles in the regulation of plant growth, development, and the response to biotic and abiotic stresses. Although they have been widely studied in many species, no information concerning TCP genes is available in sweet potato (Ipomoea batatas L.). In this study, a genome-wide analysis of TCP genes was carried out to discover their evolution and function in sweet potato. In total, 18 IbTCPs were identified and cloned. The expression profiles of the IbTCPs differed dramatically. Furthermore, four IbTCP genes of the CIN clade were found to contain miR319-binding sites. Blocking IbmiR319a significantly increased the expression level of IbTCP11/17 and resulted in a decreased photosynthetic rate due to the change in leaf submicroscopic structure, indicating the important roles of IbmiR319-targeted IbTCPs in leaf anatomical morphology. This study systematically analyzed the IbTCP gene family at a genome-wide level as well as their possible functions in leaf anatomical morphology, thus providing a foundation for further explorations of the IbmiR319/IbTCP module in association with leaf anatomical morphology in sweet potato.